1992
DOI: 10.1103/physrevlett.69.53
|View full text |Cite
|
Sign up to set email alerts
|

Explicit demonstration of the convergence of the close-coupling method for a Coulomb three-body problem

Abstract: Convergence as a function of the number of states is studied and demonstrated for the Poet-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(72 citation statements)
references
References 17 publications
1
71
0
Order By: Relevance
“…Larger basis expansions are needed to obtain convergent spin asymmetries at all angles and energies to better than 10%. Achieving significantly better convergence for the amplitudes, say to a 1% level, is likely to require a large scaling up of our present calculations based on our experience [11] with the Poet model which required 30 l = 0 states. Extrapolating to our current models, it is reasonable to suggest that a 200CC calculation could be required, which is well within the capacity of modern supercomputers.…”
Section: Resultsmentioning
confidence: 99%
“…Larger basis expansions are needed to obtain convergent spin asymmetries at all angles and energies to better than 10%. Achieving significantly better convergence for the amplitudes, say to a 1% level, is likely to require a large scaling up of our present calculations based on our experience [11] with the Poet model which required 30 l = 0 states. Extrapolating to our current models, it is reasonable to suggest that a 200CC calculation could be required, which is well within the capacity of modern supercomputers.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we have very good reasons to believe in the accuracy of the CCC method in evaluating integrated cross sections for all discrete transitions at all energies. The key issue is obtaining convergence for the transitions of interest with increasing number of expansion states [14]. Generally, the smaller the cross section, the larger the calculation necessary to obtain an accurate result.…”
Section: Convergent Close-coupling For Electron-impact Collisionsmentioning
confidence: 99%
“…A larger pseudostate basis led to a better description of the effect of the continuum ionization channel, and resolved this problem [6]. Using a model problem, Bray and Stelbovics [7,8] demonstrated that with a sufficiently large basis of eigenstates and positive-energy pseudostates convergent total cross sections could be obtained for all discrete and ionization processes at all energies, without unphysical resonance structures. Both this method, convergent close-coupling (CCC) [9,10], and the intermediate energy R-matrix (IERM) method of Burke, Scott, Sholtz and coworkers [11][12][13] were then able to accurately calculate integrated scattering cross sections (ICS) for e-H collisions over a wide range of energies.…”
Section: Introductionmentioning
confidence: 99%